1968
DOI: 10.1111/j.1365-2141.1968.tb01556.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Iron Stores on Gastric Acid Secretion by Rats

Abstract: Tissue iron deficiency as measured by liver non‐haem iron levels was produced in rats by iron‐poor diets and bleeding. Studies on gastric secretion with the Shay technique revealed significant changes in pH, total acid and acid concentration in the iron deficient rats when compared with control normals and control anaemic animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1971
1971
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However later reports indicated that long‐term treatment of humans with the proton pump inhibitor omeprazole did not induce iron deficiency [26], and treatment of rats with omeprazole only decreased iron absorption if the animals were on an iron‐deficient diet [27]. Interestingly, iron deficiency in rats has itself been reported to reduce acid secretion [28]. Further studies using other means to modify iron status are clearly required to detail the relationships between iron status and gastrin.…”
Section: Resultsmentioning
confidence: 99%
“…However later reports indicated that long‐term treatment of humans with the proton pump inhibitor omeprazole did not induce iron deficiency [26], and treatment of rats with omeprazole only decreased iron absorption if the animals were on an iron‐deficient diet [27]. Interestingly, iron deficiency in rats has itself been reported to reduce acid secretion [28]. Further studies using other means to modify iron status are clearly required to detail the relationships between iron status and gastrin.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we cannot exclude the possibility that iron overload observed in hepcidin knockout animals contributes to the reduction in gastric acid secretion. However, this scenario is unlikely, since previous studies demonstrated that iron deficiency is associated with reduced and iron overload with elevated gastric acid production/content 47 49…”
Section: Discussionmentioning
confidence: 99%